2018
DOI: 10.3390/pharmacy6030076
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and Medication-Related Problems in Hemodialysis Patients: A Call for Deprescribing

Abstract: Polypharmacy is a common problem among hemodialysis patients. It is associated with increased hospital admissions, morbidity, mortality, Medication-Related Problems (MRPs), and expenditures. There is a paucity of data on the prevalence of polypharmacy in our setting. This study aims to determine the prevalence of polypharmacy and MRPs and to assess its predictors. We conducted a cross-sectional study in the outpatient hemodialysis unit. A pharmacy resident assessed electronic prescribing records to identify MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 21 publications
6
56
0
2
Order By: Relevance
“…The majority of processes (often labelled as interventions) included medication chart review to identify any drug-related problems (DRPs) [ 15 31 ]. Many studies reported pharmacists’ interventions in: modifying drug doses and recommending new pharmacotherapy; [ 16 , 19 , 21 – 23 , 25 – 27 , 29 , 30 , 32 40 , 52 , 59 ]; interacting with a member of the multidisciplinary team; [ 15 17 , 19 21 , 23 – 25 , 27 , 31 , 32 , 34 38 , 40 43 ] requesting and monitoring laboratory parameters; [ 15 , 23 , 25 , 27 , 33 , 34 , 36 , 37 , 43 ] assessing appropriateness of medications prescribed for hospitalised patients at each point of care; [ 17 , 22 , 29 , 30 , 35 38 , 40 , 57 ]. Fewer studies described pharmacist processes at out-patient, pharmacist-led clinics relating to the management of specific CKD complications, such as anaemia; [ 34 , 39 , 44 ] hypertension and diabetes; [ 54 ] managing hypertension through telemedicine; [ 41 ] optimising dyslipidaemia management; [ 37 , 45 ] improving haemoglobin A1c levels (HbA1c); [ 43 ] and emphasising smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of processes (often labelled as interventions) included medication chart review to identify any drug-related problems (DRPs) [ 15 31 ]. Many studies reported pharmacists’ interventions in: modifying drug doses and recommending new pharmacotherapy; [ 16 , 19 , 21 – 23 , 25 – 27 , 29 , 30 , 32 40 , 52 , 59 ]; interacting with a member of the multidisciplinary team; [ 15 17 , 19 21 , 23 – 25 , 27 , 31 , 32 , 34 38 , 40 43 ] requesting and monitoring laboratory parameters; [ 15 , 23 , 25 , 27 , 33 , 34 , 36 , 37 , 43 ] assessing appropriateness of medications prescribed for hospitalised patients at each point of care; [ 17 , 22 , 29 , 30 , 35 38 , 40 , 57 ]. Fewer studies described pharmacist processes at out-patient, pharmacist-led clinics relating to the management of specific CKD complications, such as anaemia; [ 34 , 39 , 44 ] hypertension and diabetes; [ 54 ] managing hypertension through telemedicine; [ 41 ] optimising dyslipidaemia management; [ 37 , 45 ] improving haemoglobin A1c levels (HbA1c); [ 43 ] and emphasising smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies reported pharmacists’ participation in ward rounds [ 17 , 22 , 35 , 37 , 38 , 40 ], providing educational sessions to healthcare professionals [ 22 , 34 ] and performing activities such as medication use evaluations [ 34 ]. There were no reports of pharmacist prescribing activities; one study described the process of deprescribing to optimise medication use [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,28,29 Why is anticoagulation quality in HD patients with warfarin worse than that seen in patients with normal kidney function? Some of this could be explained by an increase in the number of comorbid illnesses, increased antibiotic exposure, 30 changes in intestinal flora, reduced vitamin K intake and vitamin K deficiency, 31 polypharmacy with variable adherence 32 and warfarin discontinuation or reversal for procedures.…”
Section: Inr Variability In Dialysis Patientsmentioning
confidence: 99%
“…Patients undergoing haemodialysis receive on average 10–17 regular medications, which increase the risk of inappropriate medication use, [ 1–4 ] and medication‐related problems such as improper drug selection, and absence, of indication, or adverse drug reactions. [ 5 ] Pill burden is also independently associated with a decreased health‐related quality of life.…”
Section: Introductionmentioning
confidence: 99%